2016
DOI: 10.4338/aci-2015-07-ra-0086
|View full text |Cite|
|
Sign up to set email alerts
|

User Interface Problems of a Nationwide Inpatient Information System: A Heuristic Evaluation

Abstract: SummaryIntroduction: While studies have shown that usability evaluation could uncover many design problems of health information systems, the usability of health information systems in developing countries using their native language is poorly studied. The objective of this study was to evaluate the usability of a nationwide inpatient information system used in many academic hospitals in Iran. Material and Methods: Three trained usability evaluators independently evaluated the system using Nielsen's 10 usabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 26 publications
7
31
3
9
Order By: Relevance
“…The help heuristic was placed in the group of “highest rate of problems” in three evaluated HISs. This result is consistent with the results of two previous studies ( 24 , 27 ). This finding shows that HIS designers do not pay necessary attention to help and documentation and may consider it as an unnecessary and secondary functionality ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The help heuristic was placed in the group of “highest rate of problems” in three evaluated HISs. This result is consistent with the results of two previous studies ( 24 , 27 ). This finding shows that HIS designers do not pay necessary attention to help and documentation and may consider it as an unnecessary and secondary functionality ( 28 ).…”
Section: Discussionsupporting
confidence: 94%
“…The checklist can regulate the heuristic evaluation process and avoid subjective comments about user interface problems. Secondly, although the results of this study on the HISs problems may not be generalizable to other health information systems, these results are consistent with the results of similar studies performed on HISs in many cases ( 15 , 16 , 24 , 27 ). This study also has two limitations that warrant consideration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results indicated that the heuristics "consistency and standard" and "recognition rather than recall" have the largest number of violations, with the lowest number of violations related to "error prevention" and "Help users recognize, diagnose, and recover from errors" heuristics. These results are similar to the results of other studies, such as the those conducted by Khajouei et al, Atashi et al, and Nabovati et al in Iran (25)(26)(27), and also the studies conducted by Choi and Bakken, Georgsson et al, Joshi et al, and Mirkovic et al in countries other than Iran, which reported a high number of violations concerning these heuristics (28)(29)(30)(31). On the other hand, the unexpected results of this study indicated that the severity of 60.8% of all violations is major and catastrophic, which accounts for more than half of the identified violations and, in this case, and efficiency of the systems, satisfaction of their users, and hospital's financial issues.…”
Section: Discussionsupporting
confidence: 83%
“…It was put forward by Nielsen, and after a period of development, ten usability heuristics were formally proposed in 1995 [ 24 ]. Currently, heuristic evaluation checklists developed in studies on system usability evaluation are based on the ten heuristics proposed by Nielsen as evaluation items [ 25 27 ]. Based on Nielsen’s ten usability heuristics and Shneiderman and Plaisant’s eight Golden Rules of Interface Design [ 28 ], Zhang et al [ 29 ] proposed 14 heuristics, adding items such as “informative feedback,” “clear closure,” “reversible actions” and “use user's language.” The four additional items were originally applied to determine the safety and usability of the 1-channel volumetric infusion pump used by patients.…”
Section: Introductionmentioning
confidence: 99%